A light-emitting diode motorcycle low-beam headlamp based on a freeform reflector. (May 2015) - Ge, P; Wang, X; Li, Y; Wang, H
The illumination quality of a motorcycle lighting system is essential for safety and driving comfort. In this paper, we propose a light-emitting diode (LED) motorcycle low-beam headlamp based on a freeform reflector. The reflector is generated by a freeform optics design method. Then, the optical system is simulated by the Monte Carlo method using commercial optical tracing software. The low-beam headlamp is then fabricated and assembled into a physical object. Both the simulation and measurement results show that the headlamp fully complies with United Nations Economic Commission for Europe (ECE) vehicle regulations.